A comparison of flotation performance and flotation kinetics of coal in the natural and degassed deionized water. Issue 4 (16th February 2021) - Hao, Yanan; Li, Chenwei; Zhen, Kunkun; Zhang, Haijun
ABSTRACT: The flotation performance and flotation kinetics comparative experiments of the coal were performed in different deionized water (natural and degassed). Both the cumulative combustible recovery and the modified flotation rate constant in the natural water were greater than those in the degassed water, indicating that the dissolved gases were beneficial to promote the flotation process. In addition, six flotation kinetics models were adopted to fit the flotation tests data. It was found that the first-order model with rectangular distribution had the optimal fitting degree of the results for both the natural water and degassed water. The microscope tests results showed that the coal particles were more prone to agglomeration in the natural water, which was in favor of the flotation process and responsible for the greater flotation rate.